An extensive study of the concentrations of particulate/dissolved radiocaesium derived from the Fukushima Dai-ichi Nuclear Power Plant accident in various river systems and their relationship with catchment inventory. (January 2015) - Yoshimura, Kazuya; Onda, Yuichi; Sakaguchi, Aya; Yamamoto, Masayoshi; Matsuura, Yuki
Abstract: An extensive investigation of particulate radiocaesium in suspended solids and dissolved radiocaesium in river water was undertaken at 30 sites in Fukushima and Miyagi Prefectures in December 2012, and their relationships with catchment inventory and the solid/liquid distribution coefficient ( K d ) were evaluated. Rivers located in the coastal region on the north side of the Fukushima Dai-ichi Nuclear Power Plant exhibited relatively higher particulate radiocaesium concentrations. Significant correlations were found between concentrations of particulate/dissolved radiocaesium and average catchment inventories, indicating that the concentrations of particulate/dissolved radiocaesium could be approximated from the catchment inventory. Particulate radiocaesium concentration was significantly correlated with dissolved radiocaesium concentration (with the exception of concentrations measured in estuaries), and the geometric mean K d was calculated as 3.6 × 10 5 with a 95% confidence interval of 2.6–5.1 × 10 5 . Highlights: Particulate radiocaesium concentration correlated with catchment inventory. Particulate size can be an important factor of the correlation. Solid/liquid distribution coefficients were obtained for extensive area.